The effects of rapid weight loss on aerobic and anaerobic power on athletes in weight-sensitive sports - Yadollahzadeh, R.; Jourkesh, M.; Antonio, J.; Soori, R. (Sport Science - International Scientific Journal of Kinesiology, 2015)
The purpose of this study is to investigate the impact of rapid weight loss on aerobic and anaerobic power on athletes participating in weight-sensitive sports. Twenty-four wrestlers were chosen according to standard criteria. They were informed of all procedures in the project. Participants were grouped randomly into an experimental or a control group. Before beginning the weight loss protocol aerobic and anaerobic power was calculated in each participant. The experimental group then underwent a 5 percent rapid weight loss intervention that involved heavy exercises, the use of plastic clothes, and limiting water and food consumption. t-test for correlated samples was performed to investigate within-group differences and independent samples t-test was performed for measuring the inter-group differences. After the weight loss intervention calculation was performed on research variables as the post-test. In order to determine the difference between the pre-test and post-test for the experimental and control groups, t-test was performed using SPSS software. The following results were obtained: A significant 5 percent decrease was observed for the aerobic power in the experimental group (P<0.039), and a significant increase (32 percent) in their anaerobic power (P<0.009) compared to the control group. It would read better as follows: The treatment group experienced a 5% decrease in aerobic power (P<0.039); however, anaerobic power increased 32% (P<0.009) compared to the control group.